OPDAylation of Thiols of the Redox Regulatory Network In Vitro - Madita Knieper; Lara Vogelsang; Tim Guntelmann; Jens Sproß; Harald Gröger; Andrea Viehhauser; Karl-Josef Dietz (MDPI AG, 2022)
cis-(+)-12-Oxophytodienoic acid (OPDA) is a reactive oxylipin produced by catalytic oxygenation of polyunsaturated α-linolenic acid (18:3 (ω − 3)) in the chloroplast. Apart from its function as precursor for jasmonic acid synthesis, OPDA serves as a signaling molecule and regulator on its own, namely by tuning enzyme activities and altering expression of OPDA-responsive genes. A possible reaction mechanism is the covalent binding of OPDA to thiols via the addition to the C=C double bond of its α,β-unsaturated carbonyl group in the cyclopentenone ring. The reactivity allows for covalent modification of accessible cysteinyl thiols in proteins. This work investigated the reaction of OPDA with selected chloroplast and cytosolic thioredoxins (TRX) and glutaredoxins (GRX) of Arabidopsis thaliana. OPDA reacted with TRX and GRX as detected by decreased m-PEG maleimide binding, consumption of OPDA, reduced ability for insulin reduction and inability to activate glyceraldehyde-3-phosphate dehydrogenase and regenerate glutathione peroxidase (GPXL8), and with lower efficiency, peroxiredoxin IIB (PRXIIB). OPDAylation of certain protein thiols occurs quickly and efficiently in vitro and is a potent post-translational modification in a stressful environment.